Durability Characteristics of Polyvinyl Alcohol–Treated Oil Palm Shell Concrete - Chia, Chia Thong; Ching, Delsye Lee Teo; Chee, Khoon Ng (American Society of Civil Engineers (ASCE), 2017)
This paper presents the results of an experimental study on the durability characteristics of lightweight concrete produced from agricultural waste oil palm shell (OPS) pretreated with polyvinyl alcohol (PVA) as full replacement material for conventional coarse aggregates. The tests conducted to assess the durability characteristics of PVA-treated OPS concrete are water absorption, volume of permeable voids, sorptivity, and 90-day salt ponding test in which the chloride diffusion coefficient and time to corrosion initiation are determined. The effects of different curing conditions on the durability characteristics of PVA treated OPS concrete are discussed and the results obtained are compared with raw (untreated) OPS concrete. Results show improvements in terms of water absorption, volume of permeable voids, and resistance to chloride penetration of PVA-treated OPS concrete compared with raw OPS concrete under all types of curing conditions used.